The determinants of Augmented Reality (AR) marketing affect purchase intention in the beauty and makeup industry among gen z in Malaysia. - Teo, Ke Sin; Wong, Yin Wai (2023)
Since the advancement of technology, the ways that marketers use to connect with customers between the product and customer have been changed. Although few studies have examined the relationship between a customer's purchase intent and a company's marketing strategy. Therefore, this research discusses the topic “The determinants of Augmented Reality (AR) Marketing affect purchase intention in the beauty and makeup industry among Gen Z in Malaysia.” by applying Technology Acceptance Model (TAM) to explore it. In this study, the potential factors that could affect a consumer's decision to use augmented reality (AR) to evaluate a product are critically explored. With that, the five variables proposed to this study are perceived ease of use, safety and privacy, perceived value, interactivity and purchase intention. The research instrument (a questionnaire) was given to the 384 Gen Z people who are the target respondents. Additionally, the SPSS Analysis Tool was used to look at the research data that was collected from the research tool. Reliability tests and regression models were employed to ascertain the connections between various variables. In summary, researchers and marketers can use these findings to improve the efficacy of augmented reality (AR) marketing and increase prospective customer intent to purchase.